Design of a high-voltage electrostatic ultrasonic atomization nozzle and its droplet adhesion effects on aeroponically cultivated plant roots - Gao, Jianmin; Guo, Yinan; Tunio, Mazhar Hussain; Chen, Xiangchao; Chen, Zhijian (International Journal of Agricultural and Biological Engineering, 2023)
In the process of aeroponics cultivation, the atomizer is one of the most important influencing factors on the cultivation process. This paper presented the design of an ultrasonic atomization nozzle using contact charging and a root droplet adhesion test rig. The purpose of this study was to reveal the relationship between the main operating parameters of the high-voltage electrostatic ultrasonic atomization nozzle and the atomization effect using droplet adhesion measurements. In this study, the ultrasonic effect of nozzle was achieved by using Laval tube, and the design of the key parameters for the high-voltage electrostatic ultrasonic atomization nozzle were inlet pressure, electrostatic voltage root core electrode material and spray distance; the droplet size variation and root adhesion patterns were obtained through experiments. The best operating parameters were analyzed by using the orthogonal test method, and the droplet deposition distribution of the root system at different scales was investigated in the atomization chamber. The test results revealed that when the root core electrode material was coppe and the nozzle working parameters were at 0.4 MPa of inlet pressure, at 1.75 m the spray distance, at 12 kV of the electrostatic voltage, the root system has the highest droplet adhesion.Keywords: ultrasonic nozzle, high pressure electrostatic system, droplet size measurement, root adhesion test, droplet deposition effectDOI: 10.25165/j.ijabe.20231602.7222Citation: Gao J M, Guo Y N, Tunio M H, Chen X C, Chen Z J. Design of a high-voltage electrostatic ultrasonic atomization nozzle and its droplet adhesion effect on aeroponically cultivated plant roots. Int J Agric & Biol Eng, 2023; 16(2): 30–37.